Combination of fuzzy-weighted zero-inconsistency and fuzzy decision by opinion score methods in pythagorean m -polar fuzzy environment: a case study of sign language recognition systems - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
Combination of fuzzy-weighted zero-inconsistency and fuzzy decision by opinion score methods in pythagorean m -polar fuzzy environment: a case study of sign language recognition systems by Alamoodi, Abdullah Hussein